Factors influencing food waste reduction in University Canteens: Toward sustainable campus waste management - Patranit Srijuntrapun; Pattama Ket-um (PLoS ONE, 2026)
Objective Food waste in university canteens poses a significant challenge to advancing sustainability in higher education. Context-specific, targeted strategies remain limited. This study examines the psychosocial factors influencing food waste reduction behaviors among users of university canteens in Thailand. Materials and methods Drawing on ETPB and the waste hierarchy framework, a cross-sectional survey was conducted with 400 undergraduate students in a large Thai university canteen. Data was collected through structured questionnaires and analyzed using descriptive statistics and multiple linear regression to identify key factors influencing food waste reduction behaviors. Results While responses showed consistently high levels across all dependent variables, participants engaged moderately in food waste reduction. Multiple regression analysis of the survey’s results only accounted for 17.1% of the variance in food waste reduction behaviors. Perceived behavioral control (β = 0.338, p < 0.001) and motivation (β = 0.162, p = 0.001) emerged as the strongest predictors. The study also found that structural barriers, including poor food quality (65.0%), limited portion size flexibility (36.3%), and time constraints during peak hours (58.8%), hindered upstream food waste prevention. Conclusion The findings of this study demonstrate that food waste reduction behavior amongst students is primarily driven by perceived control and motivation rather than knowledge alone. Moreover, although canteens support segregation, upstream prevention is hindered by structural barriers. These findings highlight the need for dual strategies aimed at strengthening psychosocial drivers and improving service environments, in alignment with institutional food waste policies and the global SDG 12.3 targets.